Energy Sector of the Russian Federation in the Context of Macroeconomic Instability - Savchina, Oksana V.; Savchina, Olga V.; Asinovich, Anastasia V.; Kosyakov, Maksim A.; Bobkov, Alexander L.; Bobkov, Alexander L. (International Journal of Energy Economics and Policy, 2017)
Electric power is one of the leading industries in the modern economy: it has a direct impact on all vital systems of the society per se, as well as on the formation of the social climate and on the economic development of any state. The current economic crisis and sanctions on behalf the US and the EU have significantly complicated the activities of Russian energy enterprises, thus, the government plays a key role in combating the crisis in this industry. Based on official statistical data, the article presents the results of complex analysis of the industry and defines the basic tendencies of its development. According to the results of the conducted research, it is revealed that in the past three years the performance indicators for electricity and heat production have deteriorated, the manageability of the functioning of energy systems has decreased, and the need for new technologies has increased. Keywords: state regulation, market failure, macroeconomic indicators, energy, sanctions, crisis, electricity, state support JEL Classifications: O25; Q43; Q48